OPTIMASI PENGGUNAAN KOAGULAN ALAMI BIJI KELOR (Moringa oleifera) PADA PENGOLAHAN LIMBAH CAIR MOCAF - Elida Novita; Indarto Indarto; Tris Lailatul Hasanah (Faculty of Agricultural Technology, University of Jember, 2014)
The use of moringa plant seeds as a natural coagulant has economic value and environmental friendly. They also can be used to purify water, so that the seeds were able to decrease the pollution concentration of mocaf wastewater. The aim of this research was to study the ability of moringa seeds, as a natural coagulant to overcome mocaf wastewater pollution. The method was used coagulation-flocculation with coagulant dosage range of 650 mg/l untill 1050 mg/l. The variables observed were turbidity, TSS, TDS and COD. The results showed that the optimum coagulant dose and the optimum pH is 850 mg/l and pH 8 with 59,79% decreased levels of turbidity, 75,46% TSS reduction rate and 32,55% COD reduction rate level. However the TDS values after treatment was greater than the TDS value before. It can be conclude that the use of Moringa seed powder was effective sufficiently as a coagulant for mocaf wastewater.Keywords: kelor seeds, liquid waste mocaf, turbidity, TSS, TDS and COD